Targeted Agents in Treatment of Neuroendocrine Tumors of Pancreas - Karampelas, Ilias N; Syrigos, Kostas N; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2014)
Neuroendocrine tumors (NET) of the pancreas are uncommon neoplasms that arise from the pancreatic islet cells. Surgical resections are being tested, as well as multiple chemotherapy agents. Current treatment options for nonresectable disease include somatostatin analogs and chemotherapy. New therapies focus on specific molecular targets such as sunitinib, angiogenesis inhibitor, that target vascular endothelial growth factor receptor (VEGFR) and other growth factor receptors and everolimus, an inhibitor of the mammalian target of rapamycin. Functionally based medical therapies for NET include somatostatin analogs to control symptoms. The 2014 annual meeting of American Society of Clinical Oncology (ASCO) brought us new insights into the management of pancreatic neuroendocrine tumors. The focus of this review will serve to highlight specific Abstracts (#e15160 and #e15161), that shed light on new therapeutic options that help target the unique pathways of this malignancies. Image: Athens Medical Group logo. Athens, Greece.